Engaging zwitterions in carbon-carbon and carbon-nitrogen bond- forming reactions: a promising synthetic strategy - Nair, Vijay; Menon, Rajeev S.; Sreekanth, A. R.; Abhilash, N.; Biju, Akkattu T. (Accounts of Chemical Research, 2006)
An Account of carbon−carbon and carbon−nitrogen bond-forming reactions mediated by zwitterions generated by the addition of organic nucleophiles to activated unsaturated systems highlighting their synthetic potential is presented.

Efficient higher-order cycloaddition reactions of 8,8-dicyanoheptafulvenes with dienes - Nair, Vijay; Gopalakrishnan Abhilash, K.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2007)
The cycloaddition reactions of 8,8-dicyanoheptafulvene with electron-rich dienes afforded the higher order cycloaddition products in excellent yields. With cyclic dienes as well as dimethoxybutadiene the [8+2] adducts were obtained exclusively. With methyl- and dimethylbutadienes the [6+4] adducts were the only products isolated.
Keywords: cycloadditions - bicyclic compounds - polycycles - dicyanoheptafulvene - tetrahydroazulenes

Efficient synthesis of benzofuranones: N-heterocyclic carbene (NHC)/base-catalyzed hydroacylation-stetter-rearrangement cascade - Padmanaban, Mohan; Biju, Akkattu T.; Glorius, Frank (Organic Letters, 2011)
A N-heterocyclic carbene/base-catalyzed cascade reaction leading to the formation of functionalized benzofuranones is reported. The reaction proceeds via an intramolecular hydroacylation of unactivated alkynes followed by an intermolecular Stetter reaction and a base-catalyzed chromanone to benzofuranone rearrangement.

Employing homoenolates generated by NHC catalysis in carbon-carbon bond-forming reactions: state of the art - Nair, Vijay; Menon, Rajeev S.; Biju, Akkattu T.; Sinu, C. R.; Paul, Rony Rajan; Jose, Anu; Sreekumar, Vellalath (Chemical Society Reviews, 2011)
Homoenolate is a reactive intermediate that possesses an anionic or nucleophilic carbon beta to a carbonyl group or its synthetic equivalent. The recent discovery that homoenolates can be generated from alpha,beta-unsaturated aldehydes via N-Heterocyclic Carbene (NHC) catalysis has led to the development of a number of new reactions. A majority of such reactions include the use of carbon-based electrophiles, such as aldehydes, imines, enones, dienones etc. resulting in the formation of a variety of annulated as well as acyclic products. The easy availability of chiral NHCs has allowed the development of very efficient enantioselective variants of these reactions also. The tolerance showed by NHCs towards magnesium and titanium based Lewis acids has been exploited in the invention of cooperative catalytic processes. This tutorial review focuses on these and other types of homoenolate reactions reported recently, and in the process, updates the previous account published in 2008 in this journal.

Extending nhc-catalysis: reaction of aldehydes with unconventional reaction partners - Biju, Akkattu T.; Kuhl, Nadine; Glorius, Frank (Accounts of Chemical Research, 2011)
Transition metal catalysis is a powerful means of effecting organic reactions, but it has some inherent drawbacks, such as the cost of the catalyst and the toxicity of the metals. Organocatalysis represents an attractive alternative and, in some cases, offers transformations unparalleled in metal catalysis. Unique transformations are a particular hallmark of N-heterocyclic carbene (NHC) organocatalysis, a versatile method for which a number of modes of action are known. The NHC-catalyzed umpolung (that is, the inversion of polarity) of electrophilic aldehydes, through formation of the nucleophilic Breslow intermediate, is probably the most important mode of action. In this Account, we discuss the reaction of Breslow intermediates with unconventional reaction partners.

Efficient diels-alder reaction of 1,2-benzoquinones with arynes and its utility in one-pot reactions - Kaicharla, Trinadh; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
A new protocol for the efficient Diels–Alder reaction of 1,2-benzoquinones with arynes is reported. The aryne generated by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes a facile Diels–Alder reaction with 1,2-benzoquinones, affording the dioxobenzobicyclooctadienes in moderate to excellent yields. In addition, this methodology has been applied to the one-pot synthesis of benzoquinoxalinobarrelene and naphthalene derivatives.

Efficient synthesis of gamma-keto sulfones by NHC-catalyzed intermolecular stetter reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
The N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aldehydes with α,β-unsaturated sulfones allows the atom-economic and selective formation of γ-keto sulfones in good yields. Key to the success of this unique transition-metal-free carbon–carbon bond-forming reaction is the right choice of the NHC precursor and base. The reaction tolerates a broad range of different aldehydes.

Employing arynes in transition-metal-free monoarylation of aromatic tertiary amines - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Biju, Akkattu T. (Organic Letters, 2013)
The highly monoselective N-arylation of aromatic tertiary amines using a transition-metal-free approach using arynes has been developed. The reaction afforded functionalized diaryl amines in moderate to excellent yield. High levels of functional group compatibility especially with halogen containing substrates, dyes and donor-acceptor systems, and high yields of products are the notable features of the present reaction.

Engaging isatins in solvent-free, sterically congested passerini reaction - Kaicharla, Trinadh; Yetra, Santhivardhana Reddy; Roy, Tony; Biju, Akkattu T. (Green Chemistry, 2013)
A facile, atom-economic and environmentally-benign protocol for the synthesis of biologically important oxindole derivatives in high yields has been demonstrated by employing isatins as carbonyl compound surrogates in a Passerini reaction carried out under solvent-free conditions. Moreover, electron-deficient phenols can also be used as the acid component in this reaction. In addition, the synthetic utility of the present methodology was examined by the one-pot synthesis of oxindoles with a free -OH group at the benzylic position.

Efficient synthesis of 9-aryldihydrophenanthrenes by a cascade reaction involving arynes and styrenes - Bhojgude, Sachin Suresh; Bhunia, Anup; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
A mild, general, and transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes is reported. The aryne generated by the fluoride-induced,1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes an efficient cascade reaction initiated by the Diels-Alder reaction with the differently substituted styrenes leading to the formation of 9-aryl-9,10-dihydrophenanthrene derivatives in moderate to good yields.

Employing arynes in transition-metal-free, N-heterocycles initiated multicomponent reactions - Bhunia, Anup; Biju, Akkattu T. (Synlett, 2014)
Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and various carbonyl compounds have been reported. With (iso)quinoline as the nucleophile and carbonyl compounds, such as aldehydes, ketones, and N-substituted isatins as electrophiles, the reaction afforded oxazino (iso)quinoline derivatives and the reaction proceeded via 1,4-dipolar intermediates. Interestingly, when the nucleophilic trigger used is pyridine, the reaction furnished indolin-2-one derivatives, and it is probable that the reaction proceeds via a pyridylidene intermediate.
Keywords: arynes - multicomponent reaction - oxindoles - pyridines - quinolines

Enantioselective synthesis of functionalized pyrazoles by NHC-catalyzed reaction of pyrazolones with alpha,beta-unsaturated aldehydes - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2015)
The N-heterocyclic carbene (NHC)-organocatalyzed enantioselective annulation reaction of pyrazolones with alpha,beta-unsaturated aldehydes proceeding via the chiral alpha,beta-unsaturated acyl azolium intermediates under oxidative conditions is presented. The reaction afforded dihydropyranone-fused pyrazoles in moderate to good yields and good er values under operationally simple and base-free conditions.

Employing arynes in diels–alder reactions and transition-metal-free multicomponent coupling and arylation reactions - Bhojgude, Sachin Suresh; Bhunia, Anup; Biju, Akkattu T. (Accounts of Chemical Research, 2016)
Conspectus <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Arynes are highly reactive intermediates having several applications in organic synthesis for the construction of various ortho-disubstituted arenes. Traditionally, arynes are generated in solution from haloarenes under strongly basic conditions. However, the scopes of many of the aryne reactions are limited because of the harsh conditions used for their generation. The renaissance of interest in aryne chemistry is mainly due to the mild conditions for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. This Account is focused on the Diels–Alder reaction of arynes and their transition-metal-free application in multicomponent couplings as well as arylation reactions. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">The Diels–Alder reaction of arynes is a powerful tool for constructing benzo-fused carbocycles and heterocycles. In 2012, we developed an efficient, broad-scope, and scalable Diels–Alder reaction of pentafulvenes with arynes affording benzonorbornadiene derivatives. Subsequently, we accomplished the Diels–Alder reaction of arynes with dienes such as 1,2-benzoquinones and tropones. Moreover, we uncovered a transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes by the reaction of arynes with styrenes that proceeds via a Diels–Alder/ene-reaction cascade. In addition, we demonstrated the reaction of arynes with indene/benzofurans, which proceeds via a tandem [4 + 2]/[2 + 2] sequence. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Multicomponent coupling (MCC) involving arynes mainly comprises the initial addition of a nucleophile to the aryne followed by interception of the aryl anion intermediate with an electrophile (provided the nucleophilic and electrophilic moieties do not belong to the same molecule). We have disclosed aryne MCCs initiated by N-heterocycles such as (iso)quinoline, pyridine, and aziridines. When (iso)quinoline is used as the nucleophilic trigger and N-substituted isatin as the third component, the reaction affords spirooxazino(iso)quinolines via 1,4-dipolar intermediates. Unexpectedly, using pyridine affords indolin-2-ones, where the reaction proceeds via the pyridylidene intermediate. Additionally, we developed the phosphine-triggered aryne MCCs for the synthesis of functionalized benzooxaphospholes. In another phase of our work, we studied the synthetic utility of CO2 as a one-carbon synthon in aryne MCCs for the synthesis of phthalimides. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Engaging arynes as an aryl source is one of the transition-metal-free methods for arylation reactions. We have demonstrated the N-arylation of aromatic tertiary amines and O-arylation of aliphatic alcohols using arynes. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">It is anticipated that the chemistry of arynes will continue to prosper and will lead to surprising developments for the synthesis of various 1,2-disubstituted arenes of molecular complexity and structural diversity. Future challenges in this area include the utility of arynes in enantioselective transformations and the synthesis and reactions of exotic heterocyclic arynes.
Keywords: 2-Benzoquinones; Cycloaddition; Facile N-arylation; O-arylation; One-Pot; Aldehydes; Benzyne; Amines; Heterocycles; Acids; 1

Employing carboxylic acids in aryne multicomponent coupling triggered by aziridines/azetidines - Roy, Tony; Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Thangaraj, Manikandan; Garai, Bikash; Biju, Akkattu T. (Organic Chemistry Frontiers, 2016)
The transition-metal-free aryne multicomponent coupling (MCC) involving carboxylic acids initiated by aziridines/azetidines has been reported. The use of aziridines as nucleophiles afforded N-aryl beta-amino alcohol derivatives and the application of azetidines as nucleophilic triggers furnished N-aryl gamma-amino alcohol derivatives in moderate to good yields. These reactions proceed under mild conditions and result in the formation of a new carbon-nitrogen bond and a new carbon-oxygen bond. The utility of carboxylic acids in aryne MCCs has been demonstrated, and the synthetic potential of phenols as acid surrogates in the present aryne MCCs has been realized.

Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

Enantioselective synthesis of functionalized β-lactones by NHC-catalyzed aldol lactonization of ketoacids - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
N-Heterocyclic carbene (NHC)-catalyzed intramolecular aldol lactonization of readily available ketoacids leading to the enantioselective synthesis of cyclopentane-fused β-lactones is presented. The reaction proceeds via the generation of NHC-bound enolate intermediates formed from the ketoacids in the presence of the peptide coupling reagent HATU and NHC generated from the chiral triazolium salt. The functionalized β-lactones are formed under mild conditions in high yields and enantioselectivities.

Enantioselective synthesis of spiro γ-butyrolactones by N-heterocyclic carbene (NHC)-catalyzed formal [3+2] annulation of enals with 3-hydroxy oxindoles - Mukherjee, Subrata; Joseph, Sumi; Bhunia, Anup; Gonnade, Rajesh Ghanshyam; Reddy, Santhi Vardhan; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2017)
The N-heterocyclic carbene (NHC)-catalyzed enantioselective formal [3 + 2] annulation of α,β-unsaturated aldehydes with 3-hydroxy oxindoles is presented. Under oxidative conditions using the bisquinone oxidant, the reaction resulted in the synthesis of spiro γ-butyrolactones in moderate to good yields, enantioselectivity and diastereoselectivity. The reaction likely proceeds via the generation of the NHC-bound α,β-unsaturated acylazolium intermediate from enals, which was intercepted by the dioxindoles in a formal [3 + 2] pathway to form the spirocyclic compounds. However, a deeper mechanistic investigation revealed that the reaction can also proceed via the homoenolate intermediate. In this case, the dioxindole was oxidized to the corresponding isatin derivative using traces of air under basic conditions, and was intercepted with the NHC-bound homoenolate intermediate in a formal [3 + 2] pathway to afford the spiro compound.

Employing arynes for the generation of aryl anion equivalents and subsequent reaction with aldehydes - Gaykar, Rahul N.; Bhunia, Anup; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
Arynes are highly reactive intermediates, which are utilized for the electrophilic arylation of various X-H bonds (X = O, N, S etc.). Herein, a new synthetic strategy is demonstrated, where arynes are converted into aryl anion equivalents by treatment with phosphines and a base. The addition of phosphines to arynes form the phosphonium salts, which in the presence of a carbonate base generates the aryl anion equivalent. Subsequent addition of the aryl anions with aldehydes afforded the secondary alcohols.

Enantioselective N-heterocyclic carbene-catalyzed cascade reaction for the synthesis of pyrroloquinolines via N-H functionalization of indoles - Mukherjee, Subrata; Shee, Sayan; Poisson, Thomas; Besset, Tatiana; Biju, Akkattu T. (Organic letters, 2018)
Functionalization of the indole N-H bond for enantioselective synthesis of biologically important pyrroloquinoline derivatives has been reported under oxidative N-heterocyclic carbene catalysis conditions. The interception of catalytically generated chiral alpha,beta-unsaturated acylazoliums with the indole derivatives proceeds in an aza-Michael/Michael/lactonization sequence to deliver the pyrroloquinoline derivatives in good yields, diastereoselectivities, and enantioselectivities. The simultaneous enhancement of reactivity and selectivity observed in polar aprotic solvents is noteworthy.

Enantioselective synthesis of tricyclic beta-lactones by NHC-catalyzed desymmetrization of cyclic 1,3-diketones - Shee, Sayan; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2020)
The NHC-catalyzed desymmetrization of cyclic-1,3-diketones allowing the enantioselective construction of tricyclic beta-lactones with five contiguous stereocenters, including two quaternary stereocenters, has been developed. The mild and operationally simple addition of a-bromoenals to cyclopentane-1,3-diketone derivatives proceeds via the initial formation of chiral alpha,beta-unsaturated acylazolium intermediates and culminates in a cascade reaction, following the Michael-aldol-Iactonization pathway to deliver the beta-lactone derivatives in moderate to good yields and excellent selectivity.

Enantioselective synthesis of 5,6-dihydroindolizines by N-heterocyclic carbene (NHC)-catalyzed core-structure-inspired strategy of azolium-enolate cascade - Ghosh, Arghya; Shee, Sayan; Barik, Shilpa; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2021)
The core-structure motivated design has allowed the enantioselective synthesis of 5,6-dihydroindolizines via N-heterocyclic carbene (NHC) catalysis. The NHC-catalyzed reaction of alpha,beta-unsaturated aldehydes with the suitably substituted pyrrole derivatives proceed via the initial generation of alpha,beta-unsaturated acylazoliums from enals, and enolates from pyrroles and the reaction culminated in an efficient cascade process involving the Michael-aldol-lactonization-decarboxylation sequence to afford the products in reasonable yields and high selectivities. The method is further extended to the construction of spirocyclic 5,6-dihydroindolizines.

Enantioselective synthesis of dihydrothiopyranones via NHC- catalyzed [3+3] annulation of 2-bromoenals with beta-oxodithioesters - Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2022)
The N-heterocyclic carbene (NHC)-organocata-lyzed [3 + 3] annulation of 2-bromoenals with fi-oxodithioesters resulting in the enantioselective synthesis of dihydrothiopyranones is presented. The chiral a,fi-unsaturated acylazoliums generated from 2-bromoenals and carbenes underwent smooth interception with the sulfur nucleophiles to furnish the sulfur heterocycles in satisfactory yields/selectivity. The regioselective formation of dihydrothiopyranones over the competing dihydropyranones is noteworthy.